Immigrant Entrepreneurship in United Arab Emirates: An exploratory study on East African Asian Immigrant Businesses - Khakoo, Mohamed Hussein Turabali (2008)
Immigrant entrepreneurship has always existed and has developed remarkably. It is related to migration flows over time and has brought increasing attention from researchers and management practitioners in recent years. The research sets out to investigate the process by which immigrants enter into entrepreneurship. The idea of starting a small business and the internationalization strategies they follow. A homogeneous ethnic minority is researched upon, the East African Asians who had migrated to the United Arab Emirates during the 1960’s and early 80’s. Ten qualitative semi-structured interviews were performed to gain better insight on their experiences presenting a ‘snapshot’ on their situation. Immigrant entrepreneurship can be explained by cultural, economic and institutional explanations. Findings have shown that reasons to migrate from East Africa to the United Arab Emirates where due to security, opportunity and family. These findings influenced the migrant’s decision to enter into entrepreneurship. ‘Pull’ motives were found to be the main motive behind the decision to enter into entrepreneurship. Reasons were due to opportunity, family background and previous work experience. Cultural and economic theories can explain the motives, but not the phenomenon as a whole. The role of family and social networks played a crucial role in establishing and building the business. Initially respondents’ businesses began with exporting and over time have taken bigger internationalisation steps. In addition the percentages of clients from the ethnic subgroup have decreased leading to non-reliance on ethnic networks. Findings have shown that respondents do not exhibit to be ‘sojourning’, possibly related to the family succession and policies of the country. The study concludes with limitations, implications of the research and suggestions for further research are discussed.